Nutritional Assessment and Socio-Demographic Status of Geriatric Population Residing in Bhaktapur Municipality-A Community Based Cross-Sectional Study - Duwal, Srijana; Shrestha, Alok; Kaji Poudel, Pradeep; P. Kharel, Ganga (Journal of Food Science and Technology Nepal, 2022)
The elderly remains among the most deprived in the country for several reasons, like issues with access to facilities and widespread health care needs. The cultural norms and traditional family support systems for elderly in Nepal is changing which have placed significant pressure in caring elderly people which shows an urgent need to identify and to highlight the problems the elderly people are facing, in order to bring the improvement in the quality of living. Thus, the study was conducted to assess the nutritional status, health and lifestyle of elderly aged 90 and above. Community based cross-sectional and descriptive study was carried out in Bhaktapur municipality. Semi-structured questionnaire and anthropometric measurements were used to collect information on nutritional status, socio-economic characteristics, anthropometric parameters, health and lifestyle of the elderly. The results of the study revealed that 62.8% of the total participants were at the risk of malnutrition although, most of the participants had small but frequent meals, 80% had meals at least five times a day comprising two side meals and three main meals. Despite of the age, 22.9% of the elderly lived an active life and 71.4% lived a moderate lifestyle. The results also showed that the eating pattern of long-lived elderly was characterized by regularity, simplicity and no overeating. Taken together, the report revealed that customized nutritional management and education should be developed and provided in order to improve the quality of healthy living for the elderly.